Doxylamine pharmacokinetics following single dose oral administration in children ages 2–17 years1. (18th July 2013) - Balan, Guhan; Thompson, Gary A.; Gibb, Roger; Li, Lijuan; Hull, David; Seeck, Molly
Abstract To characterize doxylamine pharmacokinetics in children. This study was conducted in 41 subjects, ages 2–17 years. Doxylamine succinate doses based on age/weight ranged from 3.125 to 12.5 mg. A single oral dose was administered with 2 to 4 oz. of water or decaffeinated beverages ∼2 hours after a light breakfast. Plasma samples were obtained before and for 72 hours after dosing and analyzed for doxylamine using HPLC MS/MS. Pharmacokinetic parameters were estimated using non‐compartmental methods and relationships with age were assessed using linear regression. Over the fourfold dose range, Cmax was similar while AUC increased only 60%, although not statistically significant (P‐value = 0.0517). As expected due to increasing body size, CLo and Vz/F increased with age. Due to a similar increase with age for Clo and Vz/F, no age‐related differences in t1/2, z were observed (∼16 hours). Allometric scaling indicated no maturation related changes in CLo; although Vz/F remained age‐dependent, the predicted range decreased ∼70%. Overall, the single doses were well tolerated. Somnolence was the most common reported AE with no apparent differences in incidence noted with age. An age/weight dosing nomogram utilizing a fourfold range of doses achieves similar Cmax, whereas AUC increases only 60%.